The Influence of Media Exposure to Marketing Information on the Travel Decision-Making of Chinese Tourists in Phuket, Thailand - Jeangjai, Supachai; Limbut, Pittaya; Wae-esor, Emeela (Journal of International Studies, Prince of Songkla University, 2025)
The purpose of this research is to study the factors affecting the decisions by Chinese tourists to travel in Phuket and to examine the influence of media exposure to marketing information on the travel decision-making of Chinese tourists in Phuket. The sample size consisted of 261 Chinese tourists selected through convenience sampling. The study found that Phuket's tourist attractions have a strong influence on Chinese tourists' decision-making. They were most satisfied with the beauty of natural attractions (x ̅ = 4.41), followed by the reputation of Phuket's tourist attractions (x ̅ = 4.32). In terms of marketing communication, the greatest influence was from the Xiaohongshu social media platform (x ̅ = 4.09), followed by the Douyin video platform (x ̅ = 3.96). The most influential media content included creative content (x ̅ = 4.28) and engaging presentation (x ̅ = 4.27).